Advancing the global public health agenda for NAFLD: a consensus statement - Lazarus, Jeffrey V.; Mark, Henry E.; Anstee, Quentin M.; Arab, Juan Pablo; Batterham, Rachel L.; Castera, Laurent; Cortez-Pinto, Helena; Crespo, Javier; Cusi, Kenneth; Dirac, M. Ashworth; Francque, Sven; George, Jacob; et al. (Nature reviews. Gastroenterology & hepatology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a potentially serious liver disease that affects approximately one-quarter of the global adult population, causing a substantial burden of ill health with wide-ranging social and economic implications. It is a multisystem disease and is considered the hepatic component of metabolic syndrome. Unlike other highly prevalent conditions, NAFLD has received little attention from the global public health community. Health system and public health responses to NAFLD have been weak and fragmented, and, despite its pervasiveness, NAFLD is largely unknown outside hepatology and gastroenterology. There is only a nascent global public health movement addressing NAFLD, and the disease is absent from nearly all national and international strategies and policies for non-communicable diseases, including obesity. In this global Delphi study, a multidisciplinary group of experts developed consensus statements and recommendations, which a larger group of collaborators reviewed over three rounds until consensus was achieved. The resulting consensus statements and recommendations address a broad range of topics — from epidemiology, awareness, care and treatment to public health policies and leadership — that have general relevance for policy-makers, health-care practitioners, civil society groups, research institutions and affected populations. These recommendations should provide a strong foundation for a comprehensive public health response to NAFLD. Non-alcoholic fatty liver disease (NAFLD) is a potentially serious liver disease with a substantial burden worldwide. In this Consensus Statement, a global multidisciplinary group of experts develop consensus statements and recommendations addressing a broad range of topics on NAFLD to raise awareness and spur action.